Pengaruh Tax Avoidance, Risiko Pajak Dan Kepemilikan Institusional Terhadap Cost Of Debt - Rachmawati, Annisa Nabila; Khoirunnisa Azzahra (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine the effect of tax avoidance, tax risk and institutional ownership on cost of debt. This research was conducted by analyzing the financial statements of companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The data collection method used purposive sampling, the data analysis technique used panel data regression, the type of data used was secondary data sourced from the company's annual report. The data used in this study is secondary data with a sample of 19 companies with 5 years of observation. The number of samples of this research is 95 financial statements. Hypothesis testing is done using the Eviews 12 application. Based on the test results, it is stated that simultaneously tax avoidance, tax risk and institutional ownership affect cost of debt. The results of research conducted partially state that tax avoidance and tax risk have no effect, while institutional ownership affects the cost of debt.